Strength and conditioning in adolescent female athletes - Sommi, C.; Gill, F.; Trojan, J. D.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2018)
Despite evidence that strength and conditioning (S&C) programs decrease injury risk and increase sport performance, young females are rarely offered S&C programs comparable to those of their male counterparts. The purpose of this study was to evaluate the current body of available literature regarding S&C in adolescent female athletes, describe potential benefits, and generate recommendations for S&C programs for female adolescent athletes. This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Systematic searches of the PubMed and Google Scholar databases were conducted using the following keywords: `female athletes,` `injury prevention,` `adolescent,` `physical fitness,` `strength,` `female adolescent,` and `conditioning.` Studies included in this review evaluated the effectiveness of S&C protocols and/or the habits and attitudes of coaches and athletic trainers working with female adolescent athletes. Seven articles evaluating S&C programs for the adolescent female athlete were used as the basis for this systematic review. These articles described current protocols and/or factors that should be taken into account when designing S&C programs. The identified articles focused on improving the strength of adolescent female athletes, decreasing the risk of injury, and exposing female athletes to the benefits of S&C that are routinely afforded to their male counterparts. Despite the critical potential benefits of S&C training, such as improved landing mechanics, coaches and athletic trainers do not routinely implement S&C programs for female adolescent athletes. The lack of such programs is largely due to misconceptions surrounding female athletes, such as the perception that females fear bulking up. S&C programs for adolescent female athletes should incorporate stretching of the hip adductors, targeted hamstring, gluteal and quadriceps strengthening, and a synergistic adaptation model, which tailors training protocols to an athlete`s pubertal stage.